The Relationship between Morning Sickness, Food Intake, and Weight Changes in Pregnant Women Aged 1 to 20 Weeks in the Working Area of the Kebomas Public Health Center, Gresik Regency - Risma Ripfandiana Sari; Rahayu Dewi Soeyono (Sean Institute, 2023)
Pregnancy is one of the phases of a woman's life during which one or more babies grow and develop inside her.The purpose of this research was to determine the relationship between the incidence of morning sickness and food intake and changes in body weight of pregnant women aged one to 20 weeks in the Working Area of the Kebomas Public Health Center, Gresik Regency. This type of research is a quantitative research with correlational method with a cross sectional approach. Respondents were pregnant women with a gestational age of one to 20 weeks in the Working Area of the Kebomas Public Health Center, Gresik Regency and were taken using the total sampling method, namely 35 pregnant women. Data was collected using the PUQE (Pregnancy Unique Quantification of Emesis). In this research, the results showed that there was a significant relationship between the incidence of morning sickness and the food intake of pregnant women aged one to 20 weeks in the Working Area of the Kebomas Public Health Center, Gresik Regency with r value = 0.006. Furthermore, the results obtained were that there was no relationship between the incidence of morning sickness and changes in the weight of pregnant women aged one to 20 weeks in the Working Area of the Kebomas Public Health Center, Gresik Regency with r value = 0.292. Thus it can be concluded that there is a significant relationship between the incidence of morning sickness and the food intake of pregnant women and there is no relationship between the incidence of morning sickness and changes in the weight of pregnant women aged one to 20 weeks in the Working Area of the Kebomas Public Health Center, Gresik Regency.